Celebrations Marking Centenary of Senate Square Uprising (1925) in Socio-Cultural Landscape of Western Siberia - K. A. Tishkina (Научный диалог)
This article focuses on the preparation and execution of events commemorating the 100th anniversary of the Senate Square Uprising. To provide a detailed examination of the topic, the research is confined to the geographical boundaries of Western Siberia. The relevance of this study is underscored not only by the enduring interest in Russian history but also by the upcoming 200th anniversary of the Decembrist uprising in 2025. The article primarily highlights the contributions of archival and museum staff in uncovering unique information about the lives and activities of exiles in Siberia. By engaging a wide array of sources, it identifies the main forms of commemoration activities, including thematic exhibitions, lectures, and reports, as well as efforts to locate burial sites of Decembrists, among others. The organization of anniversary celebrations in educational institutions across Siberia is characterized in detail. Unique aspects of the celebrations for significant anniversaries within the month are revealed, such as the 20th anniversary of the December Uprising in Moscow and the centenary of the Senate Square Uprising. It is noted that the preparatory activities sparked considerable interest in Decembrist history. The article reports that these events have facilitated a number of scholarly studies based on previously unpublished materials, while also highlighting the pressing issue of preserving and memorializing historical sites associated with the lives of exiles.